Determinants of Job Satisfaction Among Nurses: A Case of Embu Provincial Hospital - Nyarango, Jane O. (My University, 2008)
Factors affecting job satisfaction among nurses: A case of Embu Provincial General Hospital Understanding the determinants of job satisfaction is important because it has been linked inversely to staff turnover, quality of health care and clinical outcomes. The goal of the study was to identify the level and factors affecting job satisfaction among nurses working at Embu Provincial General Hospital. The study design was a descriptive cross sectional survey. A systematic random sample of 105 nurses was selected from a list of 400 nurses working in Embu Provincial Hospital. A standardized multidimensional questionnaire adopted from Mueller and McCloskey satisfaction scale was used to collect data. Data was entered using EPI info version 6 software package and later analyzed using STATA® statistical package. Descriptive statistics, correlations and logistic regression procedure techniques were used to analyze data. Findings from the study indicate that only 44.8% of the nurses were satisfied with their job. The nurses were satisfied with the organizational factors such as social support, praise/recognition, autonomy and stress levels. The respondents were dissatisfied with the following factors: pay, working environment, promotion chances and job involvement. When the organizational and demographic factors were regressed on overall job satisfaction, results showed that predictors of job satisfaction among nurses at Embu Provincial Hospital are work environment (p=0.013), Social support (p=0.028) ; and praise and recognition (p=0.039). The findings also show that organizational factors are the most important factors in determining job satisfaction in our environment compared personal correlates. The findings have implications for policy, nursing practice and further research areas.